Variabilidade da frequência cardíaca de corredores durante teste incremental máximo em esteira ergométrica - Borges, Felipe Farnesi Ribeiro (2022)
Introduction: Heart rate variability (HRV) is used in research to assess the autonomic nervous system (ANS) functioning with different applications related to human well-being. Continuous HRV monitoring is of great value, as it is possible to identify and evaluate variables related to an individual's health indexes. Objectives: HRV was analyzed during an incremental test on a treadmill, observing the behavior of the autonomic nervous system regarding the stress imposed during the test. Methods: Eleven street runners with a mean age of 31 years had the variables related to HRV captured during the incremental test on a treadmill with the aid of a Polar watch, model RS800cx, and the data obtained through the records of the RR intervals. Time domains (RMSSD, Mean RR, Mean HR, Stress Index), frequency (LF and HF) and nonlinear methods (SD1 and SD2) were analyzed. Data were compared, normalized and analyzed with resting values obtained before the start of the incremental test with the aid of the Shapiro-Wilk and One-Way ANOVA tests, with p values ≤ 0.05 being considered significant. Results: The parasympathetic, sympathetic and stress index were effective and sensitive to identify the stress imposed by the exercise during the test load increments, different from the frequency domain components (LF and HF), which did not present significant differences. In the post-exercise recovery analyzes, HRV partial recovery was found in variables analyzed 6 minutes after exhaustion, compared to resting values.